Enhancing Students' Communicative Skills through the Implementation of Task-Based Learning - Fitria Rahmawati (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to examine the effect of task-based learning implementation to enhance students' communicative skills. A one-group pretest-post-test experimental design was conducted with 37 first-year students as the participants. Video-making was selected as the assigned task. The outcomes were two short videos on the assigned topics. The results reveal that before the treatment, the students' communication skill was moderate (mean= 13.11), while after one-semester-length implementation, their skill increased and was categorized as high (15.45). Furthermore, there was a signicant difference on students' communicative skill before and after the treatment (t-value t-table = 5.585 2.021). It implies that the task-based learning through video-making task significantly enhanced students' communicative skills. Finally, some implications for language learning regarding the results of the study were also presented.